Ovarian teratoma associated with anti-NMDA (N-methyl D-aspartate) receptor encephalitis - LEEL, Nellihela (BMJ Case Rep, 2018)
Anti-N-methyl D-aspartate receptor (NMDAR) encephalitis is a paraneoplastic, immune-mediated encephalopathy with a known association with ovarian teratomas. We present the first case in the UK of a 7-year-old patient presenting with this condition. Having been previously fit and healthy, the patient presented with an acute onset of cognitive disturbances. The initial suspicion was that of an infective encephalopathy; however, the lumbar puncture results were negative. Electroencephalography reported diffuse background slowing, supporting a diagnosis of encephalopathy. Extensive autoimmune screening was done and found to be positive for anti-NMDAR antibodies. A whole body MRI found a right adnexal lesion consistent with ovarian teratoma. At laparoscopy, the right ovary was excised and histology confirmed a mature cystic teratoma with neural tissue. There were no postoperative complications with the patient’s neurology recovering progressively at follow-up.